2022
DOI: 10.1136/bmjopen-2022-062992
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of community-based rehabilitation (CBR) centres for improving physical fitness for community-dwelling older adults: a systematic review protocol

Abstract: IntroductionThe increasing ageing population has become a substantial challenge for both healthcare and social services in many Asian countries. There is a high incidence of chronic diseases and comorbidities in older populations, leading to impairments and functional disability. Functional disability may result in loss of independence, reduced quality of life and increased care needs. Community-based rehabilitation (CBR) provides rehabilitation to improve physical, mental and social outcomes. However, there i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This review was undertaken according to a published protocol [ 38 ] and reported following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines ( Supplementary Table S1 ) [ 39 ]. The review was prospectively registered on PROSPERO (CRD42021292088).…”
Section: Methodsmentioning
confidence: 99%
“…This review was undertaken according to a published protocol [ 38 ] and reported following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines ( Supplementary Table S1 ) [ 39 ]. The review was prospectively registered on PROSPERO (CRD42021292088).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous systematic review found that community-based rehabilitation can significantly improve balance and walking abilities and handgrip strength for older community-dwelling adults living in Asian countries. However, these studies did not evaluate the presence of chronic diseases and only limited research was conducted in China 25 . A Chinese self-reported survey reported that while 11.1% of older adults have been referred to CBR services, less than 1% of older adults actually receive these services 26 .…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of primary public health measures and medical advances in China, the target population of community-based rehabilitation has begun to expand to include people living in the community who need to receive long-term medical service support and health management, such as people with chronic diseases, the elderly and people with disabilities [1] . Because of the long-term nature of treatment for users receiving community rehabilitation services, in order to effectively maintain the effect of rehabilitation treatment, the use of technologies of smart medical and big data to manage users' health and form an online and offline medical and health model [2] , improve users' awareness of health maintenance will effectively help solve the problem of shortage and unbalanced optimization of medical resources as well as promote healthy communities construction [3] .…”
Section: Introductionmentioning
confidence: 99%